Adulteration and Substitution in Siddha Medical System: An Overview - Nushrath Roshana, M.; Nithiakumar, N.; Pavithra, K. (Mediterranean Journal of Basic and Applied Sciences, 2023)
Siddha Medicine is a system of Indigenous Medicine in Srilanka. Siddha Toxicology (Nanjiyeal) is very important part that is dealt with plant, animal, metal and minerals poison. According the Siddha philosophy everything found in nature has good and bad qualities (Nalvinai and Theevinai). With these ideas Adulteration and Substitution are very important part of Toxicology. Because in 20th and 21 century due to side effects of synthetic drugs, there is an increasing interest in Siddha proprietary medicines. In an International survey, herbal medicines were found to be used by approximately 70% of all over the world to maintain health. The Adulteration and Substitution of herbal drugs is the burning problem in Siddha Medicine and it has caused a major effect in the commercial use of natural products. The deforestation and extinction of many species and incorrect identification of many plants has resulted in Adulteration and Substitution of raw drugs. The future development of analysis of herbs is largely depended upon reliable methodologies for correct identification, standardization and quality assurance of Siddha drugs. Adulteration may be evaluated by Morphological or Organoleptic tests, Microscopic Evaluation, Chemical Evaluation, Physical Evaluation, Biological Evaluation and Analytical methods. This review throws light on the concepts of substitution given by our preceptors and analyses these with the present day prevailing trend of adulteration and substitution.
Keywords: Siddha medicine; Siddha toxicology; Adulteration; Substitution; Herbs